Role of piRNAs in the Drosophila telomere homeostasis. - Shpiz, S.; Kalmykova, A. (Mobile Genetic Elements, 2011)
Drosophila telomeres are maintained as a result of transpositions of specialized telomeric retrotransposons. The abundance of telomeric retroelement transcripts, as well as the frequency of their transpositions onto the chromosome ends, is controlled by a PIWI-interacting RNA (piRNA) pathway. In our recent report, we demonstrate strong evidence of piRNA-mediated transcriptional silencing of telomeric repeats in the Drosophila germline. Telomerase-generated repeats serve as a platform for recruiting specialized DNA-binding proteins which are involved in chromosome end protection and in the telomere length control. No specific proteins are known to bind to heterogeneous long sequences of the Drosophila telomeric retrotransposons. The importance of the piRNA silencing mechanism in the formation of telomeric chromatin along the region of the retrotransposon array will be discussed. We propose that Drosophila telomeric retrotransposon HeT-A serves as a template for the piRNA-mediated assembly of the specific protein complex, which is functionally similar to the recruiting of the DNA-binding telomeric proteins by the telomerase-generated repeats. The role of the piRNA pathway components in the assembly of the telomere capping complex was recently unveiled. Taken together, these data elucidate the importance of the piRNA pathway in the Drosophila telomere homeostasis.